Epitaxially grown zinc-blende structured Mn doped ZnO nanoshell on ZnS nanoparticles - Limaye, Mukta V.; Singh, Shashi B.; Date, Sadgopal K.; Gholap, Ramkrishna S.; Kulkarni, Sulabha K. (Materials Research Bulletin, 2009)
Zinc oxide in the bulk as well as in the nanocrystalline form is thermodynamically stable in the wurtzite structure. However, zinc oxide in the zinc-blende structure is more useful than that in the wurtzite structure due to its superior electronic properties as well as possibility of efficient doping. Therefore, zinc oxide shell is grown epitaxially on zinc sulphide core nanoparticles having zinc-blende structure. It is shown that doping of manganese could be achieved in zinc oxide nanoshell with zinc-blende structure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Luminescence; Nanostructures; Semiconductors; X-ray diffraction

Room temperature ferromagnetism in undoped and Fe doped ZnO nanorods: microwave-assisted synthesis - Limaye, Mukta V.; Singh, Shashi B.; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Solid State Chemistry, 2011)
One-dimensional (1D) undoped and Fe doped ZnO nanorods of average length similar to 1 mu m and diameter similar to 50 nm have been obtained using a microwave-assisted synthesis. The magnetization (M) and coercivity (H-c) value obtained for undoped ZnO nanorods at room temperature is similar to 5 X 10(-3) emu/g and similar to 150 Oe, respectively. The Fe doped ZnO samples show significant changes in M -H loop with increasing doping concentration. Both undoped and Fe doped ZnO nanorods exhibit a Curie transition temperature (T-c) above 390 K. Electron spin resonance and Mossbauer spectra indicate the presence of ferric ions. The origin of ferromagnetism in undoped ZnO nanorods is attributed to localized electron spin moments resulting from surface defects/vacancies, where as in Fe doped samples is explained by F center exchange mechanism. (C) 2010 Published by Elsevier Inc.
Keywords: Diluted magnetic semiconductors; Nanostructures; ZnO